1997
DOI: 10.1074/jbc.272.47.29911
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Basis for Insulin Resistance

Abstract: Tumor necrosis factor ␣ (TNF␣) or chronic hyperinsulinemia that induce insulin resistance trigger increased Ser/Thr phosphorylation of the insulin receptor (IR) and of its major insulin receptor substrates, IRS-1 and IRS-2. To unravel the molecular basis for this uncoupling in insulin signaling, we undertook to study the interaction of Ser/Thr-phosphorylated IRS-1 and IRS-2 with the insulin receptor. We could demonstrate that, similar to IRS-1, IRS-2 also interacts with the juxtamembrane (JM) domain (amino aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
137
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 470 publications
(143 citation statements)
references
References 45 publications
5
137
0
1
Order By: Relevance
“…In addition to insulin signaling, IRS proteins are integrally linked to intracellular signaling pathways initiated by IGF-I and the cytokines IL-2, 3, 4, 7, 9, 10, 13, 15 and IFN-␣ and IFN-␥ (2-10). Importantly, serine phosphorylation of IRS-1 blocks insulin, IGF-I, and cytokine signaling through IRS-1 (11)(12)(13)(14)(15) and appears critical to the initiation of proteasomedependent IRS-1 degradation (16,17). We have shown that chronic insulin in the presence of high glucose leads to serine phosphorylation of IRS-1 through an mTOR-dependent mechanism and that this renders IRS-1 a poorer substrate for JAK1 (18).…”
mentioning
confidence: 92%
“…In addition to insulin signaling, IRS proteins are integrally linked to intracellular signaling pathways initiated by IGF-I and the cytokines IL-2, 3, 4, 7, 9, 10, 13, 15 and IFN-␣ and IFN-␥ (2-10). Importantly, serine phosphorylation of IRS-1 blocks insulin, IGF-I, and cytokine signaling through IRS-1 (11)(12)(13)(14)(15) and appears critical to the initiation of proteasomedependent IRS-1 degradation (16,17). We have shown that chronic insulin in the presence of high glucose leads to serine phosphorylation of IRS-1 through an mTOR-dependent mechanism and that this renders IRS-1 a poorer substrate for JAK1 (18).…”
mentioning
confidence: 92%
“…Of these targets, IRS proteins have been studied widely as a major target in the TNF-induced insulin resistance. TNF-␣ has been consistently reported to inhibit insulin signaling by increasing serine phosphorylation of IRS proteins (11,(15)(16)(17). Serine phosphorylation of IRS proteins leads to IRS inhibition through at least two possibilities, which are inhibition of tyrosyl phosphorylation of IRS-1 (13,16,17), and proteasome-mediated degradation of IRS-1 (18 -21).…”
mentioning
confidence: 99%
“…Many in vitro and in vivo studies (5)(6)(7)(8)(9)(10)(11)(12)(13) have shown that increased Ser/Thr phosphorylation of IRS-1, e.g. after treatment of cells with either activators of protein kinase C (PKC), Ser/Thr phosphatase inhibitors, high insulin concentrations, or activation of cellular stress pathways by tumor necrosis factor ␣ and other cytokines, inhibits the IR-mediated tyrosine phosphorylation of IRS-1, thereby affecting insulin signal transduction.…”
mentioning
confidence: 99%